Antecedents of Employee Green Behavior in the Hospitality Industry - Khan, Noor Ullah; Cheng, Jie; Yasir, Muhammad; Saufi, Roselina Ahmad; Nawi, Noorshella Che; Bazkiaei, Hanieh Alipour (Frontiers in Psychology, 2022)
Organizations are increasingly adopting green human resource management policies so that to encourage environmentally-friendly behaviors. Research shows that adopting green policies and procedures is beneficial for the hospitality industry. However, limited empirical evidence exists related to the association between environmental-specific ethical leadership, psychological green climate, and employees’ green behavior. Therefore, this study intends to examine psychological green climate (PGC) as a mediator between the relationship of environmental-specific ethical leadership (ESEL) and employees’ green behavior (EGB), specifically in the hotel industry of Pakistan. Data from 224 non-managerial position employees in the understudy sector was collected using a convenient sampling technique. Structural equation modeling (SEM) was utilized to examine the direct and indirect effects among the variables using the Smart PLS 3.3.3 version. This study showed that ESEL is positively related to PGC and EGB. Moreover, PGC is positively associated with EGB, and PGC mediated in the relationship between ESEL and EGB. Thus, current research highlights the significance of environmental-specific ethical leadership behavior, which assists in establishing a green psychological climate, thereby fostering employees’ green behavior in the hotel industry of Pakistan.